The anti-cancer effects of itraconazole in epithelial ovarian cancer - Chel Hun Choi (Nature Portfolio, 2017)
Abstract We assessed the anti-proliferative activity of itraconazole using an EOC cell line (SKOV3ip1) and endothelial cell lines (HUVEC & SVEC4-10). We also examined angiogenesis (VEGFR2, p-ERK, p-PLCr1/2), hedgehog (Gli1, Ptch1, SMO), and mTOR (pS6K1) signaling pathways to determine the mechanism of action of itraconazole. Furthermore, we evaluated the synergistic effects of itraconazole and paclitaxel using orthotopic mouse models with established EOC cells (SKOV3ip1 or HeyA8) as well as patient-derived xenografts (PDXs). Itraconazole treatment inhibited proliferation of endothelial cells in a dose-dependent manner, but had no effect on EOC cells. The endothelial cell antiproliferative effect was associated with inhibition of hedgehog, and mTOR pathways and angiogenesis. In xenograft models of EOC using SKOV3ip1 or HeyA8, mice treated with the combination of itraconazole and paclitaxel had significantly decreased tumor weight than the control, paclitaxel-alone, or itraconazole-alone groups. Tissue derived from these tumors had significantly lower microvessel density than tissue from the other groups as well as hedgehog and mTOR pathway inhibition. We confirmed those effects in two EOC PDX models. These results suggest that itraconazole selectively inhibits endothelial cells rather than cancer cells by targeting multiple pathways including hedgehog, and mTOR pathways and angiogenesis.